SURVEI KETERAMPILAN BERHITUNG PENJUMLAHAN DAN PENGURANGAN SISWA KELAS RENDAH DI SD PADA PEMBELAJARAN MATEMATIKA - M.Syarif Sumantri; Salsa Rahmadania Safitri; Linda Zakiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to assess the numeracy skills of low-grade students in solving addition and subtraction problems, and present solution options to overcome the problems that arise. The approach used was quantitative method. The research subjects consisted of second semester low-grade students at State Elementary School 07 Petukangan Utara, Pesanggrahan District, South Jakarta City. The data collection techniques used were written tests and documentation. From the results of the study, it was concluded that overall, counting skills reached 74.85%, categorized as sufficient. Obstacles in learning arithmetic include misconceptions in operations involving zero numbers, not understanding addition and subtraction procedures, difficulty understanding story problems, and lack of accuracy in working on problems. Solutions proposed to overcome learning obstacles during the learning process include the application of math learning, providing constructive exercises and reinforcement of concepts that are not understood. Based on these conclusions, the suggestions given are that teachers should pay attention to the level of student understanding, teach concepts by emphasizing their definitions and properties, and conduct further research to reveal problems and find solutions.